Diagnosis of SARS-CoV-2 infection : preliminary results of six serology tests = Dijagnostika SARS-CoV-2 infekcije : preliminarni rezultati šest seroloških testova - Vilibić Čavlek, Tatjana (Array, 2020)
The most important use of serology in the COVID-19 diagnostics is for determination of the extent of disease in the population. However, immunoassays could represent an additional diagnostic method, especially in patients with exposure history and clinical symptoms compatible with COVID-19 who failed to be confirmed by RT-PCR. We analyzed the preliminary results of six serology tests for the diagnosis of SARS-CoV-2. Three point-of-care lateral flow chromatographic immunoassays (POC): ACRO, AMP and ENCODE and three enzyme immunoassays (ELISA): DiaPro, Vircell and Euroimmun were used. A total of 15 serum samples from COVID-19 patients and 15 serum samples from asymptomatic persons were tested. Time of sampling for COVID-19 patients was 4 – 10 days (N=4), 11 – 19 days (N=6) and 20 – 34 days (N=5) after disease onset. Initially reactive results were confirmed using a virus neutralization test (VNT). In COVID-19 patients (N=15), IgM/IgA positive detection rates were 9/60.0% (ACRO), 11/73.3% (AMP, ENCODE, Euroimmun), 12/80.0% (DiaPro) and 13/86.6% (Vircell). Overall IgG detection rates were 10//66.6% (AMP, Euroimmun) and 11/73.3% (other tests). According to the sampling time, positive detection rates were as follows: a) days 4 – 10: 1/25.0% and 2/50.0% (IgM/IgA and IgG); b) days 11 –19: 4/66.6%-6/100% (IgM/IgA), 4/66.6% and 5/83.3% (IgG); c) days 20 – 34: 4/80.0% and 5/100% (IgM/IgA), 5/100% (IgG). One asymptomatic participant tested IgM/IgA positive using ACRO, DiaPro and Vircell was confirmed seropositive using a VNT. In a group of asymptomatic persons detected seronegative using a VNT (N=14), IgM/IgA negative detection rates were 12/85.7% (ACRO), 13/92.8% (DiaPro, Vircell) and 14/100% (AMP, ENCODE, Euroimmun). IgG negative detection rates were 13/92.8% (ACRO) and 14/100% (other tests). ELISA tests showed a higher overall IgM/IgA sensitivity compared to POC tests in patients with COVID-19, while the IgG sensitivity was similar in both POC and ELISA.